2013
DOI: 10.1158/1078-0432.ccr-12-2123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor Microenvironment and Epithelial Phenotypes on Metabolism in Breast Cancer

Abstract: Purpose Cancer cells have altered metabolism, with increased glucose uptake, glycolysis, and biomass production. This study performed genomic and metabolomic analyses to elucidate how tumor and stromal genomic characteristics influence tumor metabolism. Experimental Design Thirty-three breast tumors and six normal breast tissues were analyzed by gene expression microarray and by mass spectrometry for metabolites. Gene expression data and clinical characteristics were evaluated in association with metabolic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 68 publications
5
88
0
1
Order By: Relevance
“…For example, risk factors that alter stromal content may have effects on vascular permeability, tight junction signaling, metabolic signaling, loss of contact inhibition and cell polarity. Indeed, our previous experimental work has shown that stromal-epithelial interactions altered metabolism and glucose uptake of breast cancers (41). Thus, these gene expression changes may lead to novel hypotheses about breast cancer microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, risk factors that alter stromal content may have effects on vascular permeability, tight junction signaling, metabolic signaling, loss of contact inhibition and cell polarity. Indeed, our previous experimental work has shown that stromal-epithelial interactions altered metabolism and glucose uptake of breast cancers (41). Thus, these gene expression changes may lead to novel hypotheses about breast cancer microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…In basal-like breast cancers, CAFs have increased glucose uptake, and carcinoma cells have increased OXPHOS 168 . Transcription factor A mitochondrial (TFAM) is a key transcription factor in mitochondrial biogenesis and metabolism 169 .…”
Section: Tumour Metabolismmentioning
confidence: 99%
“…Actually clinical reports from the medical staff show these subjects most suffer from advanced tumor stages. Therefore, their pathological states could be confirmed by enhanced glucose consumption and lactate production [29]. The amount of characteristic metabolites of TACE group was less than that of HCC group.…”
Section: Resultsmentioning
confidence: 99%